Chemical stability of morphine and methadone, and of methadone in combination with acepromazine, medetomidine or xylazine, during prolonged storage in syringes. Issue 8 (27th July 2017) - Lee, DY; Watson, N; Whittem, T
Abstract : Objective: To assess the chemical and physical stability of morphine and methadone stored in syringes for 12 months and of methadone when mixed with acepromazine, medetomidine or xylazine. Methods: A high‐performance liquid chromatography (HPLC) technique was developed and validated for the analysis of morphine and methadone. Morphine and methadone were dispensed into syringes and stored at 25°C/60% relative humidity (RH) and 40°C/75% RH. Solutions containing mixtures of methadone combined with acepromazine, medetomidine or xylazine were stored in syringes at 25°C/60%RH. At initiation, after 1 week and then 1, 3, 6, 9 and 12 months, samples were analysed by HPLC for the quantification of the morphine or methadone. Measured concentrations were assessed as a function of storage time and temperature using linear regression statistics to calculate stability. Results: When stored at 40°C/75%RH as pre‐dispensed syringes, severe physical and chemical changes were observed after the third month for both morphine and methadone. In contrast, at 25°C/60%RH both drugs remained chemically stable for 12 months, with concentration variations not exceeding a 5% change from initiation as stipulated in VICH stability guidelines. When in combination with acepromazine or xylazine, methadone also remained chemically stable, but the combination with medetomidine failed stability criteria prior to 6 months. Precipitation compromised the physical stability of methadone in all unsealed syringes prior to 9 months' storage. Conclusion: Pre‐dispensing morphine or methadone into unsealed syringes compromises the drugs' physical stability. Mixing of methadone with other drugs can degrade its chemical stability.